The influence of Ishraq Program as non-formal Education on Girls’ education in Upper Egypt - Mohamed, Heba Galal (AUC Knowledge Fountain, 2014)
Despite national gains in school enrollment, health, and economic development, adolescent girls in Upper Egypt are facing critical gender gaps in schooling (Isharq Program, 2013). The present research deals with how the Ishraq program, as non- formal education, has succeeded in advocating the education of adolescent girls in Upper Egypt and making their transition into formal schooling. Ishraq is a program running under an international NGO that is designed to address the educational problems in rural areas in Egypt where there are problems with schooling for young girls. Ishraq is a second chance for education that is providing necessary skills, such as literacy and life skills, reproductive health, livelihoods information, civic engagement, and sports. Ishraq provides an integrated skill-building package to be delivered in 24 months through the following categories: (1) literacy, (2) life skills, (3) sports, and (4) financial literacy in one of the five lowest-ranked governorates (Fayoum, Menya, Assiut, Qena, and Souhag), according to Human Development Index. The research gathered the primary data from the interviews and the secondary data or desk research from literature reviews, and data available online. The recent results by Ishraq report revealed that there are more than 3000 adolescent girls returning to school since the start of Ishraq in 2001 till June 2013. Moreover, the program contributed to sharing the information with their parents and neighborhoods encouraged other girls to join the program which also motivated parents to educate their girls. The Ishraq program contributed very positively towards improving literacy skills, health gains, and financial planning. The program is being assessed by the population council as one of reputable research organizations. Whereas the great challenge that is facing the program is scaling up Ishraq to a national level which causes the threats in overcoming community norms that hinder mainstreaming of Ishraq girls into formal schooling.